Two Different Phospholipases C, Isc1 and Pgc1, Cooperate To Regulate Mitochondrial Function - Balazova, Maria; Vesela, Petra; Babelova, Lenka; Durisova, Ivana; Kanovicova, Paulina; Zahumensky, Jakub; Malinsky, Jan (Microbiology spectrum, 2022)
The absence of Isc1, the yeast homologue of mammalian neutral sphingomyelinase type 2, leads to severe mitochondrial dysfunction. We show that the deletion of another type C phospholipase, the phosphatidylglycerol (PG)-specific phospholipase Pgc1, rescues this defect. Phosphatidylethanolamine (PE) levels and cytochrome c oxidase activity, which were reduced in isc1Δ cells, were restored to wild-type levels in the pgc1Δ isc1Δ mutant. The Pgc1 substrate PG inhibited the in vitro activities of Isc1 and the phosphatidylserine decarboxylase Psd1, an enzyme crucial for PE biosynthesis. We also identify a mechanism by which the balance between the current demand for PG and its consumption is controlled. We document that the product of PG hydrolysis, diacylglycerol, competes with the substrate of PG-phosphate synthase, Pgs1, and thereby inhibits the biosynthesis of excess PG. This feedback loop does not work in the absence of Pgc1, which catalyzes PG degradation. Finally, Pgc1 activity is partially inhibited by products of Isc1-mediated hydrolysis. The described functional interconnection of the two phospholipases contributes significantly to lipid homeostasis throughout the cellular architecture. IMPORTANCE In eukaryotic cells, mitochondria are constantly adapting to changes in the biological activity of the cell, i.e., changes in nutrient availability and environmental stresses. We propose a model in which this adaptation is mediated by lipids. Specifically, we show that mitochondrial phospholipids regulate the biosynthesis of cellular sphingolipids and vice versa. To do this, lipids move by free diffusion, which does not require energy and works under any condition. This model represents a simple way for the cell to coordinate mitochondrial structure and performance with the actual needs of overall cellular metabolism. Its simplicity makes it a universally applicable principle of cellular regulation.
Keywords: Mitochondria; Saccharomyces cerevisiae; fosfolipasy; Saccharomyces cerevisiae - proteiny; fosfolipasy typu C; phospholipase C; mitochondrie; fosfatidylglyceroly; Saccharomyces cerevisiae Proteins; ceramide; phosphatidylglycerol; respiration; Phosphatidylglycerols; Phospholipases; phosphatidylethanolamine; Type C Phospholipases; diacylglycerol